Real time analysis of combustion emissions: a comparison of catalyst treated and untreated solid fuels - Nyombi, Antony; Williams, Michael; Wessling, Roland (Cranfield University, 2019)
Carbon monoxide (CO) from combustion of solid fuels causes some deaths worldwide every year. This study has been undertaken to evaluate the amount of carbon monoxide, (and carbon dioxide, nitrogen oxide & methane) evolved from catalyst (Pd-Sn/alumina and Cu-Mn/graphite) treated charcoal briquettes, untreated charcoal briquettes, commercial charcoal and coal at non-isothermal temperatures between 50 to 800 oC attained at different heating rates of 20-40 (oC/min). Samples were heated in a thermal analysis instrument coupled with a multi-gas analyser under flowing air at different flow rates 20-100 (ml/min). Results showed a significant CO and NO reduction with catalyst treated charcoal compared to untreated charcoal briquettes and coal. There is also a strong dependence of CO emissions on heating rate and air flow. This study shows that catalyst treatment of solid fuels helps to minimise harmful combustion emissions.